Domínio do fato e autoria em direito penal: critérios para delimitação da autoria em face da criminalidade empresarial - Silva, Pablo Rodrigo Alflen da (2012)
This thesis starts from the idea of authorship in criminal law and has its main focus in the so-called theory of the domain of fact as guideline for delimitation of authorship. The hypothesis that is followed is that the theory of the domain of fact, presented by the German doctrine, does not present appropriate guidelines to define the authorship, especially in complex cases such as those practiced by business organizations. The result is a reformulation of the concept of domain of fact, in light of the onto-anthropological paradigm and overlooking the normative guidelines established by the Brazilian legislature. Accordingly, is proceeded to a theoretical and dogmatic review of the concept of authorship and their arrangements, in light of a new concept of domain of fact, overlooking the business crime and the aporias that underlie the complex social relationships that underpin. It is concluded that the concept of domain of fact, pragmatically useful, must start from the understanding of crime as relational and legal phenomenon and it should be guided by the idea of the result, as the offense to the legal interest.